An investigation of the relationship between pain, quality of life, and venous refill time in chronic venous insufficiency - Karaveli Cakir, Selda; Şirin, Gökçe; Eryiğit, Sinem; Çalışkan, İlknur; Toz, Hasan (SAGE Publications, 2025)
Objective Photoplethysmography provides information about global venous function and is also used to assess the time required to refill the veins within the dermis or the venous refill time. This descriptive cross-sectional study aims to investigate the relationship between pain, quality of life, and venous refill time in patients with chronic venous insufficiency. Methods The study was conducted on a sample of 72 patients diagnosed with chronic venous insufficiency. Data were collected using the Descriptive Characteristics Form, the Short-Form McGill Pain Questionnaire, and the Venous Insufficiency Epidemiological and Economic Study: The Quality of Life/Symptoms Scale (VEINES-QOL/Sym), and venous refill time was obtained by using photoplethysmography. Results The mean age of the patients included in the study was 41.24 ± 13.58 years, and 54.2% were female. A positive correlation was found between photoplethysmography and VEINES-QOL/Sym, whereas a negative correlation was found with the McGill Pain Questionnaire ( p < .001). The results showed that photoplethysmography significantly predicted VEINES-QOL/Sym and McGill Pain Questionnaire with a statistically significant correlation ( p < .001). Conclusions The results of this study indicate that venous refill time has a significant impact on both pain and quality of life. The findings underscore the need to mitigate the negative impact of CVI on quality of life in patients diagnosed with CVI. In this regard, it is of great importance to identify the factors that negatively affect the quality of life of patients with CVI and to provide counseling services for these factors.